PERSAINGAN PENGARUH DI PASIFIK SELATAN: PENGALIHAN DUKUNGAN DIPLOMATIK KEPULAUAN SOLOMON DARI TAIWAN KE TIONGKOK - Adinda Normala Putri (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2019)
The Solomon Islands shifted their diplomatic support from Taiwan to China in September 2019 after 36 years of diplomatic relations, which was followed by Kiribati, leaving Taiwan with only four South Pacific countries that still formally recognize it. China and Taiwan have long been the main actors in the competition for influence in the South Pacific, which is mainly due to the capacity of the Pacific islands to provide diplomatic recognition, where the pressure exerted by China on Taiwan has intensified since the election of Taiwan President Tsai Ing-wen in 2016. This journal discusses the motives of the Solomon Islands to turn to China, using the bandwagoning theory by Randall L. Schweller with the argument that the Solomon Islands bandwagons the wave of the future, a decision taken because the ally is considered to represent the future. The method used in this journal is a qualitative method that aims to describe and analyze a phenomenon systematically, which will explain the motive behind the Solomon Islands decision to shift its diplomatic support supported by theory and secondary data. This journal will first elaborate on China and Taiwan's rivalry in the South Pacific and continue with the Solomon Islands' motives to shift their diplomatic support from China to Taiwan. Keywords: Solomon Islands, China, Taiwan, bandwagoning Abstrak Kepulauan Solomon mengalihkan dukungan diplomatiknya dari Taiwan ke Tiongkok pada September 2019 setelah 36 tahun memiliki hubungan diplomatik, yang diikuti oleh Kiribati, meninggalkan Taiwan dengan sisa empat negara Pasifik Selatan yang masih mengakuinya secara internasional. Tiongkok dan Taiwan telah lama menjadi aktor utama dalam persaingan pengaruh di Pasifik Selatan, yang disebabkan terutama oleh kapasitas Kepulauan Pasifik untuk memberikan pengakuan diplomatik, di mana tekanan yang diberikan oleh Tiongkok terhadap Taiwan semakin intensif sejak terpilihnya Presiden Taiwan Tsai Ing-wen pada tahun 2016. Jurnal ini membahas tentang motif Kepulauan Solomon berpindah haluan ke Tiongkok, dengan menggunakan teori bandwagoning yang dicetuskan oleh Randall L. Schweller dengan argumen bahwa Kepulauan Solomon melakukan bandwagoning wave of the future, yang dilakukan karena pihak sekutu dianggap merepresentasikan masa depan. Metode yang digunakan dalam jurnal ini adalah metode kualitatif yang bertujuan menggambarkan dan menganalisa suatu fenomena secara sistematis. Metode ini akan menjelaskan motif di balik keputusan Kepulauan Solomon mengalihkan dukungan diplomatiknya didukung dengan teori dan data sekunder. Adapun dalam pembabakan jurnal ini, akan dijabarkan rivalitas Tiongkok dan Taiwan di Pasifik Selatan dan dilanjutkan dengan motif di balik keputusan Kepulauan Solomon mengalihkan dukungan diplomatiknya dari Tiongkok ke Taiwan. Kata kunci: Kepulauan Solomon, Tiongkok, Taiwan, bandwagoning